Organization of Planning in Preschool Educational Institutions - Botirova Rano Yuldashalievna (Genius Journals, 2023)
Educational process in preschool educational institutions largely depends on the quality of its planning. Planning includes setting goals, developing rules and sequences of actions, anticipating and forecasting results.
Keywords: Planning; educational institution; preschool